Antibiotic sensitivity of pathogenic bacteria isolated from beef samples obtained from Kota Bharu and its surrounding provinces - Imad Ibrahim Ali Al-Sultan; Jasbir.S; Fazlina,F. (2012)
This study investigates 42 beef samples obtained from government abattoirs and backyard slaughter houses in Kota Bharu and its surrounding provinces. The pathogenic bacteria cultured from the samples were Staphylococcus aureus, Streptococcus sp., Salmonella sp. and Escherichia coli. Sensitivity of the strains to antibiotics was determined by the Kirby-Bauer disc diffusion test. Each strain was tested against thirteen antimicrobials. Salmonella sp. and E.coli were found to be not sensitive to most of the antibiotics used (penicillin G, clindamycin, rifampin, novobiocin, amoxicillin-clavulanate and erythromycin). Most of the S.aureus strains were also not sensitive to nalidixic acid, novobiocin and erythromycin. Streptococcus species were not sensitive to novobiocin, nalidixic acid and rifampin. The study illustrates the presence of pathogenic bacteria in the beef sold in and around Kota Bharu probably due to the poor sanitary conditions during processing. It also shows the insensitivity of the bacteria to antibiotics and this may be of potential public health importance